5x-2=-3x+46

Simple and best practice solution for 5x-2=-3x+46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2=-3x+46 equation:


Simplifying
5x + -2 = -3x + 46

Reorder the terms:
-2 + 5x = -3x + 46

Reorder the terms:
-2 + 5x = 46 + -3x

Solving
-2 + 5x = 46 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-2 + 5x + 3x = 46 + -3x + 3x

Combine like terms: 5x + 3x = 8x
-2 + 8x = 46 + -3x + 3x

Combine like terms: -3x + 3x = 0
-2 + 8x = 46 + 0
-2 + 8x = 46

Add '2' to each side of the equation.
-2 + 2 + 8x = 46 + 2

Combine like terms: -2 + 2 = 0
0 + 8x = 46 + 2
8x = 46 + 2

Combine like terms: 46 + 2 = 48
8x = 48

Divide each side by '8'.
x = 6

Simplifying
x = 6

See similar equations:

| -(1/2)^2 | | 8-6x=3-5x | | 11*245+16587= | | 4^3/5 | | 5v^2-4=19v | | log(6x-5)=3 | | x^3-7x^2+4x=28 | | 24y^2-12= | | 3(-9+2x)-7x=11x-5 | | 45/9 | | My=Nx | | x^2(x^2-16)-(x^2-16)=0 | | x=3/2*3/2+3/2 | | 5/7=10/x+2 | | 24x-6-18x=2(3x-5)+4 | | 4x-9y=-4 | | 0.25x^2-6x+8=0 | | 9x-11=10+12 | | 6(2t+3)=2(9t+14) | | 0.25x^2-6x+8=y | | 2c^3+8c^2-24c=0 | | 25w^2+80w+64= | | 7h(90-h)=210 | | x^3+81x=0 | | 10b^2+19b-15= | | -6b+13=13-5b | | 4x^2+24x+35= | | 125x^3+8y^3= | | log(sub)2*(x-5)+log(sub)2*(x-3)-log(sub)2*(x)=3 | | 2n-3=51 | | 16v^2-121= | | 9(x-6)=-5x-12 |

Equations solver categories